XMM-Newton observations reveal the disappearance of the wind in 4U1630-47 - Diaz Trigo, M.; Migliari, S.; Miller-Jones, James; Guainazzi, M. (EDP Sciences, 2014)
We report on XMM-Newton observations of the black hole X-ray binary 4U 1630−47 during its 2012−2013 outburst. The first five observations monitor the source as its luminosity increases across the high−soft state of accretion. In the sixth observation the source has made a transition to an “anomalous” state, characterised by a significant contribution of electron scattering. A thermally/radiatively driven disc wind is present in the first four observations, which becomes more photoionised as the luminosity increases with time. In the fifth observation, the wind is not observed any more as a consequence of strong photoionisation and the low sensitivity of this observation. This overall trend is then consistent with a fully ionised wind causing the electron scattering characteristic of the anomalous state in the sixth observation. A broad iron emission line co-exists with the absorption features from the wind in the first four observations but is not visible in the last two observations. We find that the changes in the state of the wind as measured from modelling the absorption features with a self-consistent warm absorber model are correlated to the changes in the broad iron line. When the latter is modelled with a reflection component we find that the reflection fraction decreases as the illumination increases. We propose that the changes in both the absorption and broad emission lines are caused by the increasing luminosity and temperature of the accretion disc along the soft state. Such changes ultimately enable the transition to a state where the wind is fully ionised and consequently Comptonisation plays a significant role.